Nano-NiFe2O4 catalyzed microwave assisted one-pot regioselective synthesis of novel 2-alkoxyimidazo[1, 2-a]pyridines under aerobic conditions. Issue 15 (29th January 2016) - Payra, Soumen; Saha, Arijit; Banerjee, Subhash
Abstract : Here, we have demonstrated regioselective synthesis of novel 2-alkoxy-3-arylimidazo[1, 2- a ]pyridines using nano-NiFe2 O4 as reusable catalyst via one-pot sequential aza-Michael addition, Fe-promoted ligand transfer and C–H imination reactions. Abstract : Here, we have demonstrated an efficient and regioselective protocol for the synthesis of novel 2-alkoxy-3-arylimidazo[1, 2- a ]pyridines via microwave (MW) assisted one-pot reactions of 2-aminopyridine, β-nitrostyrenes and alcohols using nano-NiFe2 O4 as a reusable catalyst under aerobic conditions. This is the first method to produce alkoxy functionalized imidazopyridine moieties furnished via sequential one-pot three component reactions. The MW irradiation expedited the reaction rate and increased the yield of products.